PEDOMETER-MEASURED WALKING STEPS AND LEVELS OF PHYSICAL ACTIVITY: A STUDY IN KUALA NERUS, TERENGGANU - ASRI, NUR AFIFAH MUHAMAD; ALI, ASMA’; JAAFAR, SITI NUR ‘AFIFAH; JALIL, ABBE MALEYKI MHD; KAMARUDIN, KHAIRIL SHAZMIN (Malaysian Applied Biology, 2020)
The Malaysia Ministry of Health introduced the 10,000 Steps Program to embrace physical activity and increase the quality of life among the Malaysian population. Thus, this cross-sectional study aims to determine the walking steps, and level of physical activity among adults in Kuala Nerus, Terengganu. A convenience sample of 90 adults aged 18 to 59 years old had their two-days walking steps assessed using an Omron HJ-320 pedometer. Meanwhile, physical activity was measured using International Physical Activity Questionnaire (IPAQ). The Spearman correlation coefficient is used to assess the relationship between the number of walking steps based on the pedometer, and physical activity level. The result shows that the average median steps/day of the respondents was 5096 (3744). Only 6.7% of respondents achieved the 10,000 recommended steps. The respondents were generally categorized as low active for their walking steps and physical activity level. There was a significantly low relationship between physical activity and walking (r=0.214, p=0.043). This indicates that the physical activity level among respondents was relatively related by their number of walking steps. In conclusion, a pedometer can be part of an effective tool for measuring daily physical activity. Awareness programs are strongly encouraged to increase the physical activity level among the population.